Water Hyacinth Potential in The Pollution Impact Reduction of Coffee Agroindustry Wastewater - Elida Novita; Sri Wahyuningsih; Mastuki Andika; Hendra Andiananta Pradana (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2023)
Coffee processing wastewater originating from the coffee agroindustry has the potential to reduce environmental quality. Water hyacinth is one of the biological agents capable of reducing pollutants in wastewater through a rhizo-filtration mechanism in the phytoremediation process. The pollutant reducing ability of water hyacinth is limited so that the replacement of water hyacinth is one of the alternatives for optimizing the phytoremediation method. The purpose of this research was to compare the replacement time of water hyacinth to the decrease parameters namely turbidity, Biochemicals Oxygen Demand (BOD), Chemicals Oxygen Demand (COD), ammonia, and phosphate in the treatment of coffee processing wastewater using the phytoremediation method. The research stages consisted of water hyacinth acclimatization, determination of hydraulic resistance time, water hyacinth replacement time, and analysis of wastewater pollutant reduction. The density of water hyacinth used is 30 grams / L and the incubation time is 14 days. The results showed that the replacement of water hyacinth had a positive effect on improving the quality of coffee processing wastewater. The most water hyacinth replacement was on the 7th day. The percentage of turbidity parameters, Biochemicals Oxygen Demand (BOD), Chemicals Oxygen Demand (COD), ammonia (NH3-N), and phosphate (PO4-P) in the treatment of coffee processing wastewater with replacement of water hyacinth sequentially is 92.02%; 81.10%; 81.05%; 76.03% and 72.40%.